2019
DOI: 10.1021/jacs.9b01834
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Energetics of Surface Oxygen Redox from Kinetic Fingerprint in Oxygen Electrocatalysis

Abstract: The key step for rational catalyst design in heterogeneous electrocatalysis is to reveal the distinctive energy profile of redox reactions of a catalyst that give rise to specific activity. However, it is challenging to experimentally obtain the energetics of oxygen redox in oxygen electrocatalysis because of the liquid reaction environment. Here we develop a kinetic model that constructs a quantitative relation between the energy profile of oxygen redox and electrochemical kinetic fingerprints. The detailed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
170
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(188 citation statements)
references
References 73 publications
11
170
0
Order By: Relevance
“…(B) Optimized structures of single Pt atom anchored on pristine graphene (g), monovacancy graphene (g-1), and divacancy graphene (g-2), together with the associated free energy diagram for ORR, adapted with permission from Liu et al(78). (C) Activity volcano plot for ORR and the proposed mechanism, adapted with permission from Tao et al(88). (D) The difference between Gibbs free energy for two-electron and four-electron transfer ORR (G H2O − G H2O2 ) at the potential determining step and the experimental peroxide percentage on different catalysts at U RHE = 0.6 V, adapted with permission from Yang et al(89).…”
mentioning
confidence: 99%
“…(B) Optimized structures of single Pt atom anchored on pristine graphene (g), monovacancy graphene (g-1), and divacancy graphene (g-2), together with the associated free energy diagram for ORR, adapted with permission from Liu et al(78). (C) Activity volcano plot for ORR and the proposed mechanism, adapted with permission from Tao et al(88). (D) The difference between Gibbs free energy for two-electron and four-electron transfer ORR (G H2O − G H2O2 ) at the potential determining step and the experimental peroxide percentage on different catalysts at U RHE = 0.6 V, adapted with permission from Yang et al(89).…”
mentioning
confidence: 99%
“…We observed that O 2 binding at the central nitrogen of the TAPA center is stabilized by −2.59 Kcal mol −1 , and therefore, TAPA could serve as the catalytic center for the ORR. Furthermore, a plausible mechanism for the ORR has been elucidated theoretically and is given in detail in Scheme S4 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[6] The recent literature, however, reports deviations from the offset of 3.2 eV: while Viswanathan and Hansen concluded that due to solvation the intercept in the OH vs. OOH scaling is closer to 3 eV, [25] Exner determined an offset of 2.93 eV for transition-metal oxides [18] or RuO 2 -based electrocatalysts, [24] and Tao et al reported an intercept of 2.8 eV for the scaling of various metal oxides. [26] Even if the concrete intercept depends on the computational setup, such as the exchange correlation functional, the (non-negligible) span of about 0.4 eV between the reported offsets indicates that different material classes follow dissimilar scaling relations. Therefore, it is assumed that the scaling relation for the free-energy spacing of the OH and OOH adsorbate is described by an intercept between 2.6 eV and 3.6 eV, thereby considering a standard deviation of � 0.2 eV each.…”
Section: Universality In Oxygen Evolution Electrocatalysis: High-thromentioning
confidence: 98%